(untitled) (Bangladesh Journal of Zoology, 2024)
The innate immune defense system is initiated by recognizing components of microorganisms by different families of receptors such as TLRs and the intracellular NLR family. Among the NLR family, NLRC5 recognizes pathogenic components of microorganisms. The current study aimed to determine the expression profile of NLRC5 in the mucosal tissue of the oviduct of laying hens and to examine the effects of oviduct regression and estradiol benzoate (EB) on its expression. In this study, we used two groups of laying and molting hens. The molting group was treated by receiving a single dose of sesame oil or estradiol benzoate through intramuscular injection. To examine the histological differences in the oviduct between laying, molting, and estradiol-injected groups, Tissue samples from all segments of the oviduct of all groups were fixed in formalin and stained with hematoxylin and eosin. To observe the profile of NLRC5 gene and the effects of estradiol treatment, RNA was obtained from the surface epithelium and lamina propria of the whole segments of the oviduct of normal laying hens, and mucosal tissue of magnum, isthmus, uterus, and the vagina of molting groups. Both mucosal surface epithelium and lamina propria expressed NLRC5. The expression of NLRC5 was higher in the molting than in the laying group, and it was lower in the EB group. These results suggested that NLRC5 may have a role in recognizing pathogens invading the oviduct of laying and molting hens, and its expression is changed in association with oviduct growth. Bangladesh J. Zool. 51(3): 345-359, 2023